HGE antibodies in sera of patients with TBE in the Czech Republic - Zeman, Petr; Pazdiora, Petr; Cinatl, Jaroslav (International journal of medical microbiology, 2002)
Altogether 112 sera from 67 patients hospitalised for tick-borne encephalitis (TBE) were tested for the presence of antibodies against human granulocytic ehrlichiosis (HGE). Indirect immunofluorescence assay and western blotting were used for the screening and confirmation respectively. A laboratory culture of HGE agent in HL-60 cells served as an antigen supply. Commercially available human sera were used as positive controls; the respective IgG and IgM cut-offs of 1/80 and 1/40 were applied. Six patients (8.9%) exhibited specific IgG antibodies against HGE at or above the cut-off level, while no serum sample was shown to be IgM-reactive at the cut-off. The mean age of the subset of positive patients was 42 (+/- 16.7) years which exceeded that of the total TBE set averaging 37.5 (+/- 17.3) years. One patient, a woman aged 32, exhibited an elevated HGE titre of 1/80 on admission 15 days after TBE onset, that still slightly increased up to 1/160 by the end of the following week. Corresponding WB-pattern showed significant MSP, p30, and p28 bands. These findings suggest a case of concurrent TBE with HGE. Overall, this study demonstrates that TBE/HGE co-infections could be encountered in central Europe.
Keywords: fluorescenční protilátková technika nepřímá; Immunoglobulin G; Male; Seroepidemiologic Studies; séroepidemiologické studie; Immunoglobulin M; western blotting; imunoglobulin M; Česká republika; Adult; imunoglobulin G; dospělí; Ehrlichia; mužské pohlaví; Fluorescent Antibody Technique, Indirect; Encephalitis, Tick-Borne; Czech Republic; Blotting, Western; lidé; ženské pohlaví; Humans; klíšťová encefalitida; protilátky bakteriální; ehrlichióza; Female; Ehrlichiosis; Antibodies, Bacterial